Splish, splash, splat! - Scotton, Rob. (New York : Harper, 2011)
Splat does not want to have a playdate with Spike or learn how to swim, but when all of their classmates rush to the pool, Splat and Spike learn that they have something in common.
2.1
K-3
K-3
Keywords: Cats -- Juvenile fiction; Swimming -- Juvenile fiction; Cats -- Fiction; Swimming -- Fiction; Cats -- Fiction; Picture books for children; Swimming -- Fiction